2019
DOI: 10.1080/09645292.2019.1675592
|View full text |Cite
|
Sign up to set email alerts
|

Risk aversion and the teaching profession: an analysis including different forms of risk aversion, different control groups, selection and socialization effects

Abstract: SOEPpapers on Multidisciplinary Panel Data Research at DIW Berlin This series presents research findings based either directly on data from the German SocioEconomic Panel (SOEP) or using SOEP data as part of an internationally comparable data set (e.g. CNEF, ECHP, LIS, LWS, CHER/PACO). SOEP is a truly multidisciplinary household panel study covering a wide range of social and behavioral sciences:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…To summarize, statistically significant predictors included whether the student had a parent who was a teacher (+), social interests (+), one measure of cognitive ability (−), importance of having children (+), desire for professional advancement (−), desire for job security (+), and having a parent who wanted the student to become a teacher (+). The findings for social interests, importance of having children, and job security are in line with prior research (Ayaita & Stürmer, 2019;Fray & Gore, 2018;Roloff Henoch et al, 2015). Moreover, although there are clear descriptive differences in achievement and cognitive abilities between the two groups, there is only weak evidence of the negative selection hypothesis, conditional on other important predictors, confirming recent research in Germany (Roloff Henoch et al, 2015).…”
Section: Resultssupporting
confidence: 87%
“…To summarize, statistically significant predictors included whether the student had a parent who was a teacher (+), social interests (+), one measure of cognitive ability (−), importance of having children (+), desire for professional advancement (−), desire for job security (+), and having a parent who wanted the student to become a teacher (+). The findings for social interests, importance of having children, and job security are in line with prior research (Ayaita & Stürmer, 2019;Fray & Gore, 2018;Roloff Henoch et al, 2015). Moreover, although there are clear descriptive differences in achievement and cognitive abilities between the two groups, there is only weak evidence of the negative selection hypothesis, conditional on other important predictors, confirming recent research in Germany (Roloff Henoch et al, 2015).…”
Section: Resultssupporting
confidence: 87%
“…Thus, career choice will likely be influenced not only by job-specific factors such as the strength of interest in education, but also by risk preferences-not unlike choosing between low-risk but relatively low-yield bonds versus high-risk stocks that offer the prospect of much larger gain. A large-scale panel survey in Germany found that teachers tend to be more risk-averse than their peers who made other occupational choices (Ayaita & Stürmer, 2020), with similar findings about master's in education candidates compared to other graduate students in a lab-based risk preference task in at a U.S. university (Bowen et al, 2015).…”
Section: Why 'Choose and Curate'? Because The Early Career Phases Are Pivotal For Systemwide Norms Of Capability And Commitmentmentioning
confidence: 71%
“…Here, the results of previous studies indicate that teachers differ from their non-teacher counterparts according to several variables. For example, differences between (future) teachers and non-teachers could be observed with respect to vocational interests (Klusmann et al, 2009;Leon et al, 2018;Roloff Henoch et al, 2015), risk aversion (Ayaita & Stürmer, 2019), and the effects of resilience (Pretsch et al, 2012). Studies focusing on the personality trait differences between teacher candidates and students not intending to become teachers are rare.…”
Section: The Effects and Peculiarities Of Teachers' Big Fivementioning
confidence: 99%